Clinical, dermoscopic and histological features of a combined tumor composed of a melanoma in situ, a basal cell carcinoma and an intradermal naevus - Massimiliano Scalvenzi; Claudia Costa; Franco Palmisano; Gabriella Fabbrocini; Mariella Siano; Stefania Staibano (PAGEPress Publications, 2012)
The combined tumors are neoplasms consisting of 2 or more distinct cell population that are intimately admixed. The presence of more than one neoplasm in the same lesion comprising melanocytes and keratinocytes are rare but well documented. We report a case of a 65-year-old man with a melanoma in situ, a basal cell carcinoma and an intradermal naevus in collision that clinically appeared as a single lesion. Clinical, dermoscopic and histological features are discussed.